2017
DOI: 10.1111/acer.13318
|View full text |Cite
|
Sign up to set email alerts
|

Source Memory in Korsakoff Syndrome: Disentangling the Mechanisms of Temporal Confusion

Abstract: Patients with KS displayed source memory deficits, as indexed by temporal context confusions. The absence of a relationship with episodic memory performances seems to indicate that source memory impairment is not a mere by-product of amnesia. As ALC was associated with preserved source memory, the presence of temporal context confusion may serve as a complementary tool for the differential diagnosis between ALC and KS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 62 publications
0
25
0
Order By: Relevance
“…Thus, flashbulb memories seem to trigger some reliable recall for the reception context. This finding is of interest as it may suggest some positive effect of flashbulb memories on context recall, a type of recall that has been found to be particularly affected in KS patients [6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 74%
“…Thus, flashbulb memories seem to trigger some reliable recall for the reception context. This finding is of interest as it may suggest some positive effect of flashbulb memories on context recall, a type of recall that has been found to be particularly affected in KS patients [6][7][8][9][10] .…”
Section: Discussionmentioning
confidence: 74%
“…These types of memory deficits are not also noticeable in the case of chronic alcohol consumption. Following the results of the study cited, there is no continuum between the two types of neurological conditions, so chronic alcohol consumption is not characterized by a specific source of memory deficits and not always leads to the syndrome [15].…”
Section:  Alcohol-induced Dementiasmentioning
confidence: 94%
“…The psychological sample used in the above-mentioned study becomes a useful tool in making a differential diagnosis and especially to be able to capture the risk factors towards the further development of Korsakoff syndrome. Although chronic alcohol consumption does not exhibit specific memory disorders, following a detoxification treatment, these individuals are at risk of developing clinical symptoms specific to the syndrome [15].…”
Section:  Alcohol-induced Dementiasmentioning
confidence: 99%
“…KS is mainly associated with severe impairment of episodic memory. Previous studies have consistently demonstrated difficulties in patients with KS to remember the episodic context, in which information was encoded (eg, where, when, and how an item was previously encountered) 2‐9 . Another characteristic of the decline of episodic memory in KS is confabulations, 10,11 that is, the tendency of patients with KS to construct fictitious memories without an intent to deceive.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have consistently demonstrated difficulties in patients with KS to remember the episodic context, in which information was encoded (eg, where, when, and how an item was previously encountered). [2][3][4][5][6][7][8][9] Another characteristic of the decline of episodic memory in KS is confabulations, 10,11 that is, the tendency of patients with KS to construct fictitious memories without an intent to deceive. Although episodic memory impairment has been considered as the main cognitive characteristic of KS, executive dysfunction has been put forward as another prominent cognitive impairment in the syndrome, 12,13 including disinhibition, poor judgment, and planning abilities.…”
Section: Introductionmentioning
confidence: 99%